If We Treat Them, They May Live: A Single Center's Experience with Treating Neonates Born at 22 Weeks of Gestation. Issue 4 (December 2022) - Akpan, Uduak Stella; Tumin, Dmitry; Moore, Ryan
Objective: To describe a single center's experience with the management of neonates born at 22 weeks of gestation. Study Design: Retrospective review of 18 neonates born alive at 22 weeks GA to 16 mothers (cohort included 2 sets of twins) from January 2017 to December 2020, and admitted to a level IV Neonatal Intensive Care Unit. Data on antenatal management was collected from maternal charts. Results: Nine mothers delivered due to preterm labor, 5 due to preterm pre-labor rupture of membranes with intra-amniotic infection, and 2 after antepartum hemorrhage. Fourteen mothers received antenatal counseling, 75% received antenatal steroids (25% received a full course), and 31% delivered via caesarean section in honor of parental wishes. All the neonates were actively resuscitated, with 5 surviving to discharge (28%). All survivors had at least 1 morbidity at discharge. None of the infants who underwent extensive resuscitation including chest compressions, epinephrine administration, or volume expansion survived to discharge. Conclusions: Adequate antenatal counseling with personalized decision-making consistent with parental desires is the preferred approach at the limits of viability. Although not evident in this study, antenatal interventions such as corticosteroids may improve outcomes and should be considered for families who desire neonatal resuscitation at 22 weeks.